Characterisation and technological aspects of yeasts isolated from raw milk and different types of cheeses produced in Argentina - Carrasco, Marta Susana (2006)
A total of 116 yeast strains were isolated from raw milks, whey of different cheeses manufactures and soft and hard argentinian cheeses. The different types of cheeses were sampled for yeasts isolation during all processing, before and after the ripening process and ready for marketing, and included both the inner part and the surfaces of the cheeses. Yeasts were enumerated in cheeses samples after 1, 6, 10 and 15 days (soft cheeses), and 1, 3 and 6 months (hard cheeses) of ripening and in milks, whey, natural whey cultures and commercial lactic starter cultures at time of use for cheesemaking. The strains isolated were identified using standard conventional identification methods indicated by Kreger van Rij (1984) and Barnett et al. (2000). API tests were also applied for the identification. In order to evaluate their potential incorporation at cheese starter cultures, some technological properties such as growth at different temperature and pH values, and tolerance to different concentrations of NaCl were tested. The results obtained showed yeasts were present in all cheeses samples examined, at number ranging from 10 CFU/g to 4,5.105 CFU/g of cheese, while the incidence levels in milks and whey were from 10 to 5.103 CFU/ml and from 10 to 2.104 CFU/ml respectively. In natural whey cultures and commercial lactic starters cultures yeasts were not detected. Candida (50 %) and Geotrichum (50 %) prevailed in milks, Candida (42,2 %), Cryptococcus (21 %) and Trichosporon (36,8 %) were the genera found in whey, while Candida was the genus predominant in cheeses. Less frequently isolated genera were Brettanomyces and Schizosaccharomyces. Results from this study also showed association among species predominant in milks and that present in different cheese varieties. Candida famata was predominant in all raw milks and cheeses examined. All studied strains were able to growth at different pH values and at 15 and 18°C, and some of them also exhibit psychrotrophic aptitude. All strains were also able to growth in the presence of 2,5 and 10% NaCl, while the ability to growth in presence of 15 and 20% NaCl was variable for each strain. On the basis of these results and a further technological characterization, the selection of the yeast strains isolated from raw milks and cheeses for potential incorporation at cheese starter cultures is warranted.